Synthesis of ultrathin ZnO, nylon-6, 6 and carbon nanofibers using electrospinning method for novel applications. (2021) - Kale, Subodh M.; Kirange, Piyush M.; Kale, Tushar V.; Jee Kanu, Nand; Gupta, Eva; Chavan, Sachin S.; Kumar Vates, Umesh; Kumar Singh, Gyanendra
Abstract: The following study is based on three experimental works; synthesis of ultrathin (a) ZnO nanofibers, (b) nylon-6, 6 nanofibers, and (c) carbon nanofibers using electrospinning method. ZnO, nylon-6, 6, and carbon nanofibers are having potential applications in defense, aerospace, and automotive industries to improve the mechanical properties such as strength, rigidity, and good stability under heat or chemical resistance; for manufactured products. Zinc Oxide (ZnO) is used in a wide range because of its nontoxicity. Carbon nanofibers are used because of its high flexibility and it is stable in organic as well as inorganic molecules. The nanofibers are used for solar cells (ZnO nanofibers), air purification (nylon-6, 6 nanofibers), and water purification (carbon nanofibers). Synthesis of nanofibers is done by electrospinning its solution. Scanning electron microscopy (SEM) was used to characterize the diameter of the electrospun nanofibers. The solutions are prepared using (a) formic acid (HCOOH) to dissolve nylon-6, 6, (b) dimethylformamide (DMF) to dissolve zinc acetate and polyvinylpyrrolidone at room temperature, and (c) DMF to dissolve polyacrylonitril (PAN). The SEM images are analyzed for the average diameters of different nanofiber mats for defense, biomedical, and environmental applications.